(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Objective: Studies on hormonal changes is an effective method for assessing infertility conditions. A widely used pesticide 1, 2 Dibromo 3 Chloropropane (DBCP) causes infertility by damaging testis in humans. This in turn disturbs Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH), sex steroid hormone levels. The seed extract of Mucuna pruriens (M. pruriens) is well known antioxidant and is expected to improve the sperm quality after exposure to DBCP. Method: Male Sprague-Dawley rats were divided into four Groups. Group I – Control received 0.9% saline, Group II – single dose of 50mg/kg 1, 2-Dibromo 3 Chloro Propane (DBCP)dissolved in Dimethyl sulphoxide (DMSO) (1ml) was administered for 30 days, Group III – Methanolic extract of Mucuna pruriens (200mg/kg body weight) was administered for 45 days after 50mg/kg of 1,2 dibromo 3 chloropropane (DBCP) treatment (30 days).Group IV – 200mg/kg/day BW methanolic extract of M. pruriens for 45 days. Results:The body, testis, and epididymis weights of all the rats were taken. DBCP induced group II toxicity bearing animals were significantly decreased when compared to group I control animals. In group II DBCP-induced toxicity rats, there was a reduction in sperm morphology, concentration, and motility as well as follicle stimulating hormone (FSH), testosterone, and luteinizing hormone (LH) levels. DBCP-induced group II toxicity-bearing animals’ above-mentioned parameters improved after treatment with Mucuna pruriens seed extract. Conclusion: The administration of M. pruriensseed extract improves sperm quality and Hormone levels in the DBCP exposed group III rats.